194k views
4 votes
Helpppp pleaseeee !!!!

Helpppp pleaseeee !!!!-example-1

2 Answers

1 vote

You need only substitute x= 7 and calculate it.


f(7) = 3/(7+2) - √(7-3) = 3/9 -√4= 1/3 - 2 = 1/3 - 6/3=-5/3 ≈ -1.67


f(7) = - 1.67

Answer : -1.67.



User Daniel Von Fange
by
5.5k points
5 votes

When x = 7


Plug in 7 for x


-----------------------------------------------------------------------------------------------------------------


f(x) = (3/(x + 2)) - √(x - 3)


f(7) = (3/(7 + 2)) - √(7 - 3)


-----------------------------------------------------------------------------------------------------------------


First simplify each parenthesis.


7 + 2 = 9

7 - 3 = 4


f(7) = (3/9) - √(4)


-----------------------------------------------------------------------------------------------------------------


Simplify. Divide 3 with 9, and root 4


f(7) = 1/3 - 2


-----------------------------------------------------------------------------------------------------------------


Subtract


f(7) = 1/3 - 2


f(7) = 1/3 - 6/3


f(7) = - 5/3


-----------------------------------------------------------------------------------------------------------------


Answer: f(7) = -5/3


-----------------------------------------------------------------------------------------------------------------


hope this helps

User Murlakatam
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.